2017
DOI: 10.1101/cshperspect.a022194
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Family Signaling in Epithelial Differentiation and Epithelial–Mesenchymal Transition

Abstract: Epithelia exist in the animal body since the onset of embryonic development; they generate tissue barriers and specify organs and glands. Through epithelial-mesenchymal transitions (EMTs), epithelia generate mesenchymal cells that form new tissues and promote healing or disease manifestation when epithelial homeostasis is challenged physiologically or pathologically. Transforming growth factor-βs (TGF-βs), activins, bone morphogenetic proteins (BMPs), and growth and differentiation factors (GDFs) have been imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 238 publications
(345 reference statements)
7
88
0
Order By: Relevance
“…TGF-β signals through cell surface type I transmembrane receptors, which heterodimerize with the type II receptors, leading to activation of canonical Smad2/3/4 pathways and Smad independent pathways including: Rho, p38MAPK and PI3 kinase. These signaling pathways regulate the actin cytoskeleton and gene expression of cell cycle regulators, cytokines matrix proteins and proteases [16, 17]. The role of TGF-β signaling in breast fibroblasts during breast cancer progression is complex.…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β signals through cell surface type I transmembrane receptors, which heterodimerize with the type II receptors, leading to activation of canonical Smad2/3/4 pathways and Smad independent pathways including: Rho, p38MAPK and PI3 kinase. These signaling pathways regulate the actin cytoskeleton and gene expression of cell cycle regulators, cytokines matrix proteins and proteases [16, 17]. The role of TGF-β signaling in breast fibroblasts during breast cancer progression is complex.…”
Section: Introductionmentioning
confidence: 99%
“…The process of nerve navigation during tooth development is strictly regulated by signalling networks, such as semaphorin 3A, 40 TGF‐β 41 and activin signalling, 42 and closely associated with tooth morphogenesis. Recent studies illuminate that in mice incisor, sensory nerve fibres secrete sonic hedgehog protein to activate Gli1 + cells, which is a critical subpopulation of MSCs differentiating into odontoblasts and pulp cells 5 .…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that this outcome may be a result of EMT being affected in ESCC. EMT is an important process in cancer metastasis, with 90% of tumors exhibiting different degrees of EMT during tumor development . During this process, the epithelial cells attenuate the expression of epithelial characteristics and gain mesenchymal phenotype properties .…”
Section: Discussionmentioning
confidence: 99%
“…EMT is an important process in cancer metastasis, with 90% of tumors exhibiting different degrees of EMT during tumor development. [33][34][35] During this process, the epithelial cells attenuate the expression of epithelial characteristics and gain mesenchymal phenotype properties. 36,37 In this study, we surprisingly found that blocking FGFR4 suppressed EMT in ESCC cells, including the upregulation of epithelial markers (E- cadherin and Claudin-1) and the downregulation of mesenchymal markers (N-cadherin, Vimentin, and Snail).…”
Section: Discussionmentioning
confidence: 99%